2021
DOI: 10.1111/jpy.13172
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the harmful alga,Prymnesium parvum(Prymnesiophyceae), after gradual and abrupt increases in salinity

Abstract: Prymnesium parvum is a euryhaline, toxin‐producing microalga. Although its abundance in inland waters and growth potential in the laboratory is reduced at high salinity (>20), the ability of inland strains to adjust their growth after long‐term residence in high salinity is uncertain. An inland strain of P. parvum maintained at salinity of 5 in modified artificial seawater medium (ASM‐5) was subjected to the following treatments over five sequential batch culture rounds: ASM‐5 (control); modified ASM at salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We obtained Hi-C scaffolded, highly contiguous genome assemblies of two P. parvum strains from Texas: UTEX 2797 and 12B1. UTEX 2797 was selected for sequencing due to its use in numerous toxicology and physiology experiments of P. parvum ( e.g., 19,20,22,[27][28][29][30][31][32]. However, preliminary analysis of k-mer frequencies revealed that UTEX 2797 displays high sequence-level heterozygosity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained Hi-C scaffolded, highly contiguous genome assemblies of two P. parvum strains from Texas: UTEX 2797 and 12B1. UTEX 2797 was selected for sequencing due to its use in numerous toxicology and physiology experiments of P. parvum ( e.g., 19,20,22,[27][28][29][30][31][32]. However, preliminary analysis of k-mer frequencies revealed that UTEX 2797 displays high sequence-level heterozygosity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…is more than 100 nmol L −1 (Pennington and Scott 2001; Weiner et al 2004), which is much higher than the concentrations we used in this study. There may be some unknown mechanisms in these species to compensate for atrazine stress and keep their carbon uptake less affected (Weiner et al 2007; Richardson and Patiño 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Lundgren et al [292] looked into biotic factors that may influence bloom formation in Texas estuarine waters and reported that the seasonal composition of planktonic communities may complicate P. parvum's establishment in these waters. Based on these observations, Richardson and Patiño [293] suggested that biotic and abiotic conditions in the upper reach of intertidal zones may be serving as barriers to downstream expansion. Research into these and other possible scenarios could help understand-and maintain-current barriers to the seaward expansion of P. parvum blooms in Texas.…”
Section: Haptophytesmentioning
confidence: 97%